Penentuan Jarak Antar Tiang Penerangan Jalan Umum Untuk Jalan Lurus Dan Jalan Melengkung Pada Jalan Tol Ruas Lingkar Luar Jakarta W2 Utara Seksi I - Ersalia Dewi Nursita (Energi & Kelistrikan, 2020)
The Jakarta Outer Ring Road North W2 Section I has a different road width and also an interchange that is curved like a circle. On this toll road the distance between the piles used in both type of road is the same, that is equal to 30 m. Determination of the distance between the poles of the street lighting for straight roads and curved paths in this thesis using the phytagoras method. Where the distance between the lampposts for a straight road with the width of the road ranges from 4.5 m to 14.5 m from the calculation results require the distance between piles of 21.09 to 29.85 (<30 m) this results in less lighting standard. And for the width of the road ranging from 15.5 m to 30.5 m from the calculation results require the distance between the piles of 31.01 m to 50.82 m (> 30 m) which results in waste in the installation of the number of poles. Whereas for curved roads with a road width of 7.5 m for the placement of light poles in the arches of the road requires a smaller distance between piles of 20.96 m (<30 m).